-3(x-5)=33

Simple and best practice solution for -3(x-5)=33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-5)=33 equation:


Simplifying
-3(x + -5) = 33

Reorder the terms:
-3(-5 + x) = 33
(-5 * -3 + x * -3) = 33
(15 + -3x) = 33

Solving
15 + -3x = 33

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + -3x = 33 + -15

Combine like terms: 15 + -15 = 0
0 + -3x = 33 + -15
-3x = 33 + -15

Combine like terms: 33 + -15 = 18
-3x = 18

Divide each side by '-3'.
x = -6

Simplifying
x = -6

See similar equations:

| 20=5+5x | | (2+5*2.7)=7000 | | 10x-(5x-10)=5+4x | | 16.9+12.1= | | 4(x-4)+7x=7x-12 | | (6h)h=2 | | 9x+7=9+8x | | 7x+4+15x-2=90 | | 4x+8=10+6x | | uk+uq=x | | -x^3-2x^2+13x-10=0 | | 370=15y+25x | | (6y-5)(36y^2+30y+25)= | | 48-y=-4y+7 | | 40=2w+2l | | P=5-b+c | | -(x+2)=-2 | | h^2-hk-2k^2=0 | | 2(x-4)+6=4x-2(3+x) | | x+x=127 | | x^2-4x-2y-6=0 | | 21x-21=22x | | f(x)=10x+0 | | -5y+21=-7(y-1) | | 6-16x=2x-12 | | .15x+50=77 | | -4(y+3)=3y-19 | | 14+11x+6=14x+29 | | 5v=44-6v | | 6x-9=3(x-4) | | -44+4x=-7 | | (8x^3-5x^2+3)+(6x^3+9x^2-10)+(-8x^3+8x^2-4)= |

Equations solver categories